Autonomous and portable device for rapid sample-to-answer molecular diagnostics at the point-of-care - Witters,D; Jue,E; Schoepp,NG; Begolo,S; Rodriguez-Manzano,J; Shen,F; Maamar,H; Shur,A; Ismagilov,RF (2020)
In this work, we demonstrate a novel prototype of an autonomous, equipment-free, and handheld device that integrates sample preparation, on-board storage of liquid and dry reagents, nucleic acid amplification, and cellphone based detection in point-of-care (POC) and limited resource settings (LRS). We demonstrate sample preparation from urine samples within 4 min and minimal hands-on time (<1 min), as well as amplification of target nucleic acids within 15 min on-device. The proposed prototype was validated for the detection of Neisseria gonorrhoeae in urine samples within 20 min.